2014
DOI: 10.1088/1674-1056/23/4/047502
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic resonance frequency shift model of laminated magnetoelectric structure tuned by electric field

Abstract: Based on Smith-Beljers theory and classical laminate theory, an explicit model is proposed for the ferromagnetic resonance (FMR) frequency shift of a stress-mediumed laminated magnetoelectric structure tuned by an electric field. This model can effectively predict the experimental phenomenon that the FMR frequency increases under a parallel magnetic field and decreases under a perpendicular magnetic field when the electric field ranges from −10 kV/m to 10 kV/m. Besides, this theory further shows that the FMR f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Therefore, the ferromagnetic resonance frequency and working frequency range of the nonreciprocal ME filter will be changed. According to the electrically tunable FMR frequency shifting model established by Zhou et al, [13] a concise expression of the coefficient A is written as…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the ferromagnetic resonance frequency and working frequency range of the nonreciprocal ME filter will be changed. According to the electrically tunable FMR frequency shifting model established by Zhou et al, [13] a concise expression of the coefficient A is written as…”
Section: -2mentioning
confidence: 99%
“…The magnetoelectric composite materials and multiferroic film possess the capability of controlling magnetism and the ability of tuning ferromagnetic resonance by an electric field applied to the piezoelectric phase through magnetoelectric (ME) coupling. [8][9][10][11][12][13] Due to the magnetization controlled by the electrostatic field or voltage, the magnetoelectric coupling mechanism may contribute to the formation of a series of RF/microwave magnetoelectric devices [14][15][16] in the future, whose frequency and bandwidth are magnetoelectric tunable. At present, the magnetoelectric tunable filter, [17,18] the magnetoelectric resonator, [19,20] the magnetoelectric phase shifter, [21][22][23][24] and antenna [25][26][27] are representative.…”
Section: Introductionmentioning
confidence: 99%
“…So, it can be described by an equivalent magnetic field δ H E(i) = AE i induced by the electric field. The expression of the ME conversion factor A is given as [54]…”
Section: Lumped-equivalent Circuit Model Of Me Filtermentioning
confidence: 99%
“…[11,12] This technique has gained great attention largely due to its simple operation, high accuracy, and high speed of inspection. [13][14][15][16][17] MO imaging method is proved to be an effective way to detect and track the micro weld joint during laser welding. It is found that the weld joint position of MO image will change with different magnetic field intensity, and almost not change at different welding speeds.…”
Section: Introductionmentioning
confidence: 99%